The Effect Of Applying Somatic Auditory Visual (SAVI) Approach On Students’ Speaking Achievement In Oral Descriptive Text Of 2018/2019 Eleventh Year Students’ Of SMA Yayasan Pendidikan Harapan Bangsa Kabupaten Langkat - Ummi Umara - (Jurnal Serunai Bahasa Inggris, 2018)
ABSTRACT This study is conducted as an attempt to find out the effect of applying SAVI approach on Students’ speaking Achievement in oral descriptive text. This study used the experimental design. The population of this study is the students of SMA Yayasan Pendidikan Harapan Bangsa . The sample of this study was the 2018/2019eleventh grade students of SMA Yayasan Pendidikan Harapan Bangsa . This study is conducted with two randomized groups namely experimental group and control group. The control group is taught by conventional method while experimental group is taught by applying SAVI Approach. The instrument used in this study was an oral test. To obtain the reliability of the test, the researcher used t-test formula.. The data were analyzed by using t-test. The calculation shows that t-observed (2.50) is higher than t-table (1.666) at the level of significance (α) 0.05 with the degree of freedom (df) 74. Therefore, null hypothesis (Ho) is rejected and alternative hypothesis (Ha) is accepted. It means that SAVI approach significantly affect the students’ speaking achievement in oral descriptive text.